ChemInform Abstract: Tandem Broensted Acid Promoted and Nazarov Carbocyclizations of Enyne Acetals to Hydroazulenones. Issue 22 (13th May 2013) - Escalante, Luz; Gonzalez‐Rodriguez, Carlos; Varela, Jesus A.; Saa, Carlos
Abstract The reaction proceeds under metal‐free conditions and allows the access to various bicyclic products consisting of a cyclopentenone and a 7‐membered moiety.